The Microeconomics of Income Distribution Dynamics in East Asia and Latin America - Bourguignon, Francois (Washington, DC: World Bank and Oxford University Press, 2013)
This volume presents a collection of studies on the dynamics of income inequality based on micro data. Using a simple but powerful empirical methodology, the authors analyze the roles of prices, occupational choice, and educational choice in accounting for household income and its contribution to inequality. It casts doubt on the grand theories of growth and income inequality that have dominated discussions in development economics. It paves the way for a full-blown, micro-based general equilibrium theory of income determination and income inequality.